Assembly of P3HT/CdSe nanowire networks in an insulating polymer host. Issue 25 (14th June 2018) - Heo, Kyuyoung; Miesch, Caroline; Na, Jun-Hee; Emrick, Todd; Hayward, Ryan C.
Abstract : Hybrid nanowire networks of electron donors and acceptors were achieved by the combination of phase separation, interfacial segregation, and crystallization in multicomponent blends. Abstract : Nanoparticles may act as compatibilizing agents for blending of immiscible polymers, leading to changes in blend morphology through a variety of mechanisms including interfacial adsorption, aggregation, and nucleation of polymer crystals. Herein, we report an approach to define highly structured donor/acceptor networks based on poly(3-hexylthiophene) (P3HT) and CdSe quantum dots (QDs) by demixing from an insulating polystyrene (PS) matrix. The incorporation of QDs led to laterally phase-separated co-continuous structures with sub-micrometer dimensions, and promoted crystallization of P3HT, yielding highly interconnected P3HT/QD hybrid nanowires embedded in the polymer matrix. These nanohybrid materials formed by controlling phase separation, interfacial activity, and crystallization within ternary donor/acceptor/insulator blends, offer attractive morphologies for potential use in optoelectronics.